2008
DOI: 10.1007/s10329-008-0110-5
|View full text |Cite
|
Sign up to set email alerts
|

Predation on giant flying squirrels (Petaurista philippensis) by black crested gibbons (Nomascus concolor jingdongensis) at Mt. Wuliang, Yunnan, China

Abstract: Predation on vertebrates is infrequent in gibbons. In a 14-month field study of the central Yunnan black crested gibbon (Nomascus concolor jingdongensis) at Mt. Wuliang, Yunnan, China, we observed gibbons attacking, killing and eating giant flying squirrels (Petaurista philippensis). During 845 h of observation on one study group, the gibbons attacked giant flying squirrels 11 times, and succeeded in 4 cases. Although all members of the group attempted to attack the squirrels, all four successful attacks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…They also exchanged grooming with the adult male and groomed each other (Fan et al 2006). They even shared meat when 1 female killed flying squirrels (Fan and Jiang 2009). We recorded few cases of agonism among adults during the study.…”
Section: Social Relationships Between Membersmentioning
confidence: 98%
See 1 more Smart Citation
“…They also exchanged grooming with the adult male and groomed each other (Fan et al 2006). They even shared meat when 1 female killed flying squirrels (Fan and Jiang 2009). We recorded few cases of agonism among adults during the study.…”
Section: Social Relationships Between Membersmentioning
confidence: 98%
“…FB is likely to be the mother of this juvenile. Our previous study showed that the juvenile slept with FB on 1 night (Fan and Jiang 2008a) and that she always shared meat with him when she killed flying squirrels (Fan and Jiang 2009). The juvenile male usually slept with the adult male at night (Fan and Jiang 2008a), but this study shows that they did not maintain a close spatial relationship throughout the day.…”
Section: Social Relationships Between Membersmentioning
confidence: 99%
“…Three preliminary studies have described social relationships among the adults in the polygynous western black crested gibbon ( Nomascus concolor ) [Fan & Jiang, ; Fan et al, ; Huang et al, ]. At the Wuliang study site, an adult male and two breeding females formed a stable social group [Fan & Jiang, ]. Both females groomed the adult male and the two females were observed to groom each other [Fan et al, ], feed in the same trees, and sometimes share food [Fan & Jiang, ].…”
Section: Introductionmentioning
confidence: 99%
“…Early accounts of wild primates were often purely anecdotal (see examples from the late eighteenth and early nineteenth centuries in Zuckerman []) before animals were habituated and more quantitative methods for data collection became standard (Altmann ; Burghardt ). Some of the most interesting primatological discoveries of the last one hundred years, such as tool use and hunting, came out first in the form of anecdotal accounts (Goodall ) and were then identified and analyzed across the field (on tool use, see Beck ; Breuer, Ndoundou‐Hockemba, and Fishlock ; Galdikas ; Van Schaik, Deaner, and Merrill ; Visalberghi ; Watanabe, Urasopon, and Malaivijitnond ; on hunting, see Butynski ; Fan and Jiang ; Fedigan ; Goffe and Fischer ; Hosaka et al. ).…”
Section: Anecdotal Evidence Within Primatologymentioning
confidence: 99%